2006
DOI: 10.1161/01.str.0000249056.24657.8b
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Risk Factors for Stroke and Transient Ischemic Attacks in Middle-Aged Men

Abstract: Background and Purpose-The impact of lipometabolic and glucometabolic disturbances on stroke incidence remains to be characterized in detail. We investigated relations of a comprehensive panel of baseline lipometabolic and glucometabolic variables to incident fatal and nonfatal stroke or transient ischemic attack (TIA), and stroke subtypes. Methods-A community-based prospective study of 2313 middle-aged men invited to a health survey at age 50. Results-During a follow-up of up to 32 years, 421 developed stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
66
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 43 publications
5
66
0
1
Order By: Relevance
“…Circulating fatty acids provide an objective measure of exposure, and are thus less subject to random error. However, previous studies that have used circulating PUFA as exposure have not produced consistent findings (6)(7)(8)(14)(15)(16)(17)(18)(19)(20)(21) . Therefore, the aim of our study was to investigate the associations between serum n-3 and n-6 PUFA and risk of stroke in men.…”
mentioning
confidence: 85%
“…Circulating fatty acids provide an objective measure of exposure, and are thus less subject to random error. However, previous studies that have used circulating PUFA as exposure have not produced consistent findings (6)(7)(8)(14)(15)(16)(17)(18)(19)(20)(21) . Therefore, the aim of our study was to investigate the associations between serum n-3 and n-6 PUFA and risk of stroke in men.…”
mentioning
confidence: 85%
“…Due to the occurrence of any disease over time, the population at risk will be transformed into a population of survivors. The FA composition characterized by high levels of palmitoleic and oleic acids and low intake of linoleic acid is previously shown to be associated with mortality 8 and stroke 36 in the ULSAM cohort. Therefore, we sought to investigate the effect of competing risk by death in the present study.…”
mentioning
confidence: 92%
“…The relative risk of FFA composition in serum samples has been studied in human cerebral ischemic events [17,20]. Iso et al reported that ischemic stroke is associated with changes in FFA; a higher intake of fish and n−3 polyunsaturated fatty acids is associated with a reduced risk of ischemic stroke, suggesting that FFA may have a role in protecting against ischemic stroke via a specific pathway in lipid metabolism [21].…”
Section: Introductionmentioning
confidence: 99%